Oxidative Deoximation of Heterocyclic Ketoximes by Quinolinium Fluoro Chromate-A Kinetic and Mechanistic Approach - Vimala, T.; Jani Bai, T.S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of 2,6-diphenyl piperidin-4-one oxime (PPO) and its 3- alkyl substituted by quinolinium fluorochromate (QFC) in aqueous acetic acid 60 % (v/v) leads to the formation of corresponding ketones. The reaction is first order each in quinolinium fluorochromate and the oximes. The acidity dependence is fractional order throughout the entire range of acidities studied. Variation in ionic strength has no perceptible change in the rate. The steric effect plays a dominant role to decide the rate of the reaction and the reactivity sequence observed is 3-H > 3-Me > 3-Et > 3,3-diMe > 3-iPr.